2016
DOI: 10.1002/jms.3835
|View full text |Cite
|
Sign up to set email alerts
|

Changes in grape polyphenols (V. vinifera L.) as a consequence of post‐harvest withering by high‐resolution mass spectrometry: Raboso Piave versus Corvina

Abstract: Grape dehydration is an oenological process used for the production of high-quality reinforced and sweet wines. Corvina and Raboso Piave are two red grape varieties used for production of high-quality Italian wines, such as Recioto, Amarone di Valpolicella and Raboso Passito. Changes of polyphenolic composition of the grapes as a consequence of the withering were studied by ultra-high performance liquid chromatography-quadrupole time of flight mass spectrometry (UHPLC/QTOF); for identification of compounds a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
(104 reference statements)
2
21
0
Order By: Relevance
“…In contrast, in on‐vine withered samples, the increase in trans ‐resveratrol was not substantial and also piceatannol increased to a lesser extent. These findings match previous studies on in‐warehouse withered Raboso grapes . In particular, during dehydration, an increase in the expression of stilbene synthase (STS) was found in parallel with the increase of trans ‐resveratrol in grape .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, in on‐vine withered samples, the increase in trans ‐resveratrol was not substantial and also piceatannol increased to a lesser extent. These findings match previous studies on in‐warehouse withered Raboso grapes . In particular, during dehydration, an increase in the expression of stilbene synthase (STS) was found in parallel with the increase of trans ‐resveratrol in grape .…”
Section: Resultssupporting
confidence: 90%
“…In contrast, in the in‐warehouse grapes, only E ‐ϵ‐viniferin showed a relevant and statistically significant increase. A previous study on warehouse dehydration of three grape varieties (Raboso Piave, Corvina and Molinara) carried out under controlled conditions slightly different from those used here (18 °C, RH 40%, air flow 0.4 m s −1 ) showed that the E / Z ‐ ϵ ‐viniferin ratio increases during withering . Findings of the study would indicate that this parameter can also be useful to distinguish off‐vine and on‐vine dehydrated grapes.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…To our knowledge, these compounds have not previously been found in fig. Isorhamnetin‐3‐ O ‐glucoside and syringetin were found in grape and blueberry, tamarixetin in grape …”
Section: Resultsmentioning
confidence: 81%
“…Many analytical methods with various detection techniques are reported for the separation and identification of individual stilbenes in edible berries, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Vrhovsek et al 2012), liquid chromatography-mass spectrometry (LC-MS) (Može et al 2011), liquid chromatography with dual detection by a photodiode array and quadrupole time-of-flight mass spectrometry (LC-PDA-QTOF/MS) (Samoticha et al 2017), high-pressure liquid chromatography-mass spectrometry (HPLC-MS) (Bavaresco et al 2002;Jiang et al 2012;Kiselev et al 2017), high-pressure liquid chromatography with diode array detection (HPLC-DAD) (Bavaresco et al 2002;Sun et al 2006;Vilanova et al 2015;Guerrero et al 2010aGuerrero et al , 2016, high-pressure liquid chromatography with UV detection (HPLC-UV) (Vincenzi et al 2013;Kawakami et al 2014;He et al 2009a), ultra-high-pressure liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC/QTOF/MS) (Flamini et al 2016;De Rosso et al 2016), ultra-performance liquid chromatography with dual detection by a photodiode array and fluorescence detectors (UPLC/DAD/FL) (Samoticha et al 2017), ultra-performance liquid chromatography with dual detection by a diode array and tandem quadrupole mass spectrometry (UPLC/ DAD/TQD) (Guerrero et al 2010a), gas chromatography-mass spectrometry (GC-MS) (Ragab et al 2006;Viñas et al 2009Viñas et al , 2011, gas chromatographymass spectrometry with selected ion monitoring (GC-MS SIM) (Rimando and Cody 2005), gas-liquid chromatography with flame ionization detection (GLC-FID) (Moriartry et al 2001), capillary electrophoresis (CE) (Ehala et al 2005) and high-speed counter-current chromatography (HSCC) (He et al 2009b). Various methods are used for analyses of stilbenes contents in the edible berries are different which could also contribute to the observed variability in the published results.…”
Section: Isolation and Identification Of Stilbenes In Edible Berriesmentioning
confidence: 99%